Private content delivery network (CDN) implementation: a case study of MARA network infrastructure / Mohd Saifullizam Jaafar - Jaafar, Mohd Saifullizam (2013)
Recently, majority of organization was fully equipped with the ICT infrastructures physically and aided with systems application based on web content to ease information sharing. The advancement of web content manipulation either in static or dynamic, the size of content increasingly large expands and it causes to burden the content accessing on the internet. Therefore, one of the solutions for the content adaptations and accelerate the content browsing through the Content Delivery Network (CDN) technology. Usually based on several literature reviews, CDN technology was eminently practical and effective to accelerate widely delivery content around the globe which involves various ISP networks. However these techniques also have several drawbacks whether in commercial CDN, P2P CDN or hybrid CDN, it does not guarantee to data integrity, data ownership and security of the content because it involving third party resources and it difficult to takes it under fully control. Meanwhile, based on the problem statement it leads to the case study in MARA organisation. MARA has several branches around Malaysia that equipped with ICT infrastructures and also has the various web content system that were published to be accessed by majority of end users located around Malaysia. Furthermore, the preliminary investigation and supported previous research clearly indicates that current situation lead to the following objectives: (I) to design and develop DNS Geolocation Malaysia Regional Aware, (II) to validate the design of MARA Private CDN by region overall, (III) to evaluate the effectiveness of PCDN. In order to achieve the stated objectives this research applied a methodology which consists of five phases: (i) problem specification (ii) solution design (iii) implementation (iv) evaluation and (v) conclusion. As a result, this research found that PCDN can accelerate the local content in Malaysian region and afford to overcome the load access consistently in peak period by distributing burden between CDN nodes. In a nutshell, the PCDN give a lot of advantages to the organization which have many branches in accelerating access by using the current resources. Also it could save from data integrity, ownership and content security because it does not use sourced from third party. Finally, implementing PCDN means that an organization’s security certificates are retained within the walls of the corporation, not given out to a vendor.